Red Neuronal Artificial ART2 para la agrupación de datos - Rodríguez, Jorge E (Revista Científica, 2006)
In this paper, we present a partial advance of the project of development investigation of,tools for data mining, which consists on the implementation of Adaptative Resonance Network (ART2) for the clustering data. The implemented technique is compared with Self-Organizing Maps and the algorithm EM (Expectatión Maximization) with the púrpose of measuring the clustering effectiveness.